giải các phương trình :
a) \(\sqrt{-x^2+x+4}=x-3\)
b)\(\sqrt{-2x^2+6}=x-1\)
c) \(\sqrt{x+2}=1+\sqrt{x-3}\)
giải phương trình
a)\(\sqrt{x+6-4\sqrt{x+2}}+\sqrt{x+11-6\sqrt{x+2}}=1\)
b)\(\sqrt{x-2+\sqrt{2x-5}}+\sqrt{x+2+3\sqrt{2x-5}}=7\sqrt{2}\)
giải phương trình
\(\sqrt{x^2-4x+4}-2x+5=0\)
Giải phương trình:
a. \(\sqrt{x^2-2x+5}=x+1\)
b. \(\sqrt{x^2+5x-2}=x-3\)
c. \(\sqrt{x^2-1}+1=x^2\)
d. \(x-\sqrt{x^4-2x^2+1}=1\)
Giải phương trình:
\(\sqrt{x-1+2\sqrt{x-2}}+\sqrt{7+x+6\sqrt{x-2}}=2\)
\(\sqrt{x+2+3\sqrt{2x-5}}+\sqrt{x-2-2\sqrt{2x-5}}=2\sqrt{2}\)
Giải phương trình:
a. \(\sqrt{x^2-2x+1}+\sqrt{x^2-6x+9}=1\)
b. \(\sqrt{x+2\sqrt{x-1}}+\sqrt{x-2\sqrt{x-1}}=2\)\(\)
c. \(\sqrt{x+3+4\sqrt{x-1}}+\sqrt{x+8+6\sqrt{x-1}}=1\)
Giải phương trình:
a) \(\dfrac{1}{x+\sqrt{1+x^2}}+\dfrac{1}{x-\sqrt{1+x^2}}+2=0\)
b) \(2x-5a\sqrt{x-a}+2a\left(a-1\right)=0\) với a>0
Giải phương trình:
a. \(\sqrt{x^2+2x+1}=9\)
b. \(\sqrt{1-4x+4x^2}=5\)
c. \(\sqrt{x^2-2x\sqrt{2}+2}=5\)
d. \(\sqrt{4x^2-4x+1}-\sqrt{9x^2}=0\)
e. \(\sqrt{x^2-2x+1}-\sqrt{3+2\sqrt{2}}=0\)
1. Giải phương trình: \(\sqrt{\left(4+x\right)\left(6-x\right)}=x^2-2x-12\)
2. Giải phương trình: \(3\left(x^2-6\right)=8\left(\sqrt{x^3-1}-3\right)\)